Analisis keterampilan menulis teks negosiasi dengan metode quantum learning - Siti Ana Nur Alfiaturrohmah; Cahyo Hasanudin; Ahmad Kholiqul Amin (Jurnal Genre (Bahasa, Sastra, dan Pembelajarannya), 2021)
Negotiation text is a text that contains a bargain which aims to reach an agreement between two parties who have common interests. This study aims to determine the form of the structure of the negotiating text, namely the form of orientation, request, fulfillment, offer, approval, purchase, closing. This research is a qualitative descriptive study using a case study approach with 23 students as subjects. The results showed that the tenth grade students of MA Asy-Syukuriyah wrote the structure of the negotiating text on the orientation, request, fulfillment, offer, approval, purchase, closing sections categorized as very good. The conclusion of this study is that users of the quantum learning method can make students write negotiating texts well.